2013
DOI: 10.1680/jees.2013.0018
|View full text |Cite
|
Sign up to set email alerts
|

The disinfection efficacy of chlorine and chlorine dioxide as disinfectants of Bacillus globigii, a surrogate for Bacillus anthracis, in water networks: A comparative study

Abstract: Intentional contamination of drinking water with anthrax spores is a concern to water utilities. The spores may become embedded in the distribution pipe corrosion and biofilm, where they will be protected from residual disinfectants. This paper compares the disinfection effectiveness of chlorine and chlorine dioxide on Bacillus globigii , a surrogate for B. anthracis . Batch experiments were performed using both disinfectants. Data was analyzed using the delayed Chick-Watson model to determine the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…While extensive biofilm growth has been observed in cooling towers, the efficacy of different biocide application regimens on biofilm communities in cooling towers is not known. In addition, persistent survival of even a small number of organisms in biofilms can serve as a source of rapid recolonization of the system following any interruption of biocide treatment (Hosni et al 2009), but the extent and rate of bacterial re-growth from these communities following treatment also is not known.…”
Section: Introductionmentioning
confidence: 99%
“…While extensive biofilm growth has been observed in cooling towers, the efficacy of different biocide application regimens on biofilm communities in cooling towers is not known. In addition, persistent survival of even a small number of organisms in biofilms can serve as a source of rapid recolonization of the system following any interruption of biocide treatment (Hosni et al 2009), but the extent and rate of bacterial re-growth from these communities following treatment also is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Morrow et al (2008) also demonstrated monochloramine to be more effective at disinfecting B. anthracis Sterne and B. thuringiensis spores in a biofilm than chlorine, corroborating previous reports that monochloramine is more stable and is less reactive toward the biofilm matrix (LeChevallier et al 1990; Griebe et al 1994). Hosni et al (2009), using the same experimental method as Szabo et al (2007), found that ClO 2 was able to penetrate the biofilm matrix much better than chlorine and inactivate 4 log 10 CFU of biofilm associated BG spores with 25 mg L −1 within 8 days.…”
Section: Biofilms and Amoebamentioning
confidence: 94%
“…Hosni et al (2009) conducted ClO 2 susceptibility testing of B. globigii at a slightly lower temperature (20 °C, pH 8), and reported a 2 log 10 Ct of 76, comparable to B. anthracis spores (57 and 73 for B. anthracis Stern and Ames, respectively, Table 1). Side-by-side comparisons of the surrogate spores and B. anthracis spores should be conducted before selecting an appropriate surrogate spore for ClO 2 disinfection.…”
Section: Use Of Surrogatesmentioning
confidence: 99%
“…Most disinfection approaches have been evaluated using B. anthracis surrogates, such as Bacillus subtilis, Bacillus globigii and Bacillus cereus. [7][8][9][10] Recommendations by the Environmental Protection Agency (EPA) include mainly chemical disinfectants, among which are sodium hypochlorite and liquid chlorine dioxide. 6 According to previous studies, viable spore counts may be reduced more than two logs within 2 h when using chlorine dioxide, while free chlorine achieves minimal spore inactivation (2 log reduction after 7 h at 1 mg L −1 free chlorine) and even higher concentrations are required when spores are embedded in biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…6 According to previous studies, viable spore counts may be reduced more than two logs within 2 h when using chlorine dioxide, while free chlorine achieves minimal spore inactivation (2 log reduction after 7 h at 1 mg L −1 free chlorine) and even higher concentrations are required when spores are embedded in biofilms. 5,7 Although these chemicals have exhibited certain efficacy against the Bacillus spores, considerable health hazards and destructive properties are associated with them. 10 Therefore, there is a quest for alternative disinfection methods, especially when human contact occurs or sensitive equipment and materials are present.…”
Section: Introductionmentioning
confidence: 99%